Surface defects in semiconductor lasers studied with cross-sectional scanning tunneling microscopy - Richard Cobley (Applied Surface Science, 2010)
Cross-sectional scanning tunneling microscopy is used to study defects on the surface of semiconductor laser devices. Step defects across the active region caused by the cleave process are identified. Curved blocking layers used in buried heterostructure lasers are shown to induce strain in the layers above them. Devices are also studied whilst powered to look at how the devices change during operation, with a numerical model that confirms the observed behavior. Whilst powered, low-doped blocking layers adjacent to the active region are found to change in real time, with dopant diffusion and the formation of surface states. A tunneling model which allows the inclusion of surface states and tip-induced band bending is applied to analyze the effects on the tunneling current, confirming that the doping concentration is reducing and defect surface states are being formed.